GLOBAL CITIZENSHIP IN PLURALISTIC SOCIETY: THE ROLE OF EDUCATION GLOBAL CITIZENSHIP AS STRATEGIC INSTRUMENTS - Kartika Safitri; Aim Abdulkarim; Kokom Komalasari (SOSIOEDUKASI, 2026)
The era of globalization has fundamentally transformed modern society, creating greater cross-national interdependence and increasing the need for cross-cultural understanding. This article examines the concept of global citizenship and its role in fostering social cohesion within increasingly pluralistic societies. Using a comprehensive literature review approach, the study analyzes the definition of global citizenship, the characteristics of global and pluralistic societies, and the role of citizens in responding to contemporary social challenges. The findings indicate that Global Citizenship Education (GCE) serves as a strategic instrument for developing the knowledge, skills, values, and attitudes required for active participation in an interconnected world. The study identifies several key challenges in implementing GCE, including curriculum integration, educator capacity, local cultural resistance, unequal access to educational resources, and difficulties in assessing learning outcomes. As a contribution to the existing literature, this article offers an integrated analytical framework that connects global citizenship, pluralism, implementation challenges, and educational strategies within a single discussion, providing a more comprehensive understanding of GCE in contemporary contexts. Strategic recommendations include curriculum development, teacher professionalization, multi-stakeholder collaboration, and the effective use of educational technology. The study concludes that GCE represents a long-term investment in preparing future generations to become responsible global citizens capable of contributing to a more peaceful, inclusive, and sustainable world.